PENGARUH LATIHAN SERVIS BAWAH TERHADAP KEMAMPUAN SERVIS BAWAH PADA TIM BOLA VOLI PUTRI MAN 1 PEKANBARU - Annam, Mhd Khairul; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The issues raised in this research is that the ability of the service under the womwn’s volleyball team MAN 1 Pekanbaru is still not good,this can be seen when the women’s team to service under a lot of balls that are still not over the net,and also the direction the ball is not maximized.this is caused by a lack of technical training services under the women’s volleyball team MAN 1 Pekanbaru, so that when the women’s team to services, there are many directions ball does nt enter into the field or off the field.the lack of a player’s ability to perform services under volleyball possibility is caused by lack of trained technical service under women’s volleyball team MAN 1 Pekanbaru. Bisides the lack of a player’s ability to perfom under proper servicing is caused by a lack of proper training program to train service capabilities under womwn’s volleyball team.This form of exercise is a study with experimental treatment. The population in this study is the women’s volleyball team MAN 1 Pekanbaru, the sample in this study is a population which total 12 people. Data collection techniques derived from the pre-tes and post-test. The instruments used in this research are under the service, which aims to measure the ability of a service under.the variables that exist in this study is lower servicing exercise denoted by X as the independent variable, whereas with lower servicing capabilities represented by Y as the dependent variable. After the data is processed with statistical, normality test with liliefors test at significant level of 0.05a. the hypothesis is the effect of exercise services are under the lower servicing capabilities. Based on the result of t test analysis , T result is 5,728 and T table is 1,796, it means T result > T table . It can be concluded that Ha is accepted, it concludes that there is a significant influence on the service under the service under the women’s volleyball team MAN 1 Pekanbaru.Key Words: Lower Servicing Exercise